Week 96 resistance analyses of the once‐daily, single‐tablet regimen (STR) darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) in adults living with HIV‐1 from the phase 3 randomized AMBER and EMERALD trials. Issue 6 (15th February 2021) - Lathouwers, Erkki; Weinsteiger, Shirley; Baugh, Bryan; Ghys, Anne; Jezorwski, John; Mohsine, El Ghazi; Van Landuyt, Erika; De Meyer, Sandra
Abstract: In AMBER and EMERALD, darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg demonstrated high virological response and low virological failure (VF) through week 96. Week 96 resistance analyses are presented. Post‐baseline samples for genotyping/phenotyping were analyzed from protocol‐defined‐VFs with viral load (VL) ≥ 400 copies/ml at failure/later time points. Post‐hoc analyses were deep sequencing (AMBER) and HIV‐1 proviral DNA sequencing from baseline samples (VL < 50 copies/ml) (EMERALD). Through week 96 across studies, no darunavir, primary protease inhibitor (PI), or tenofovir resistance‐associated‐mutations (RAMs) occurred in patients continuing ( N  = 1125) or switching to D/C/F/TAF ( N  = 715). M184I/V (emtricitabine RAM) was detected in one patient in each arm of AMBER. In EMERALD D/C/F/TAF patients with prior VF and baseline genoarchive data ( N  = 98), 4% had darunavir RAMs,  36% emtricitabine RAMs, mainly at position 184 (32%), 4% tenofovir RAMs, and 19% ≥3 thymidine‐analogue‐associated‐mutations at screening. The predicted phenotype showed 0% had reduced susceptibility to darunavir, 37% to emtricitabine, and 22% to tenofovir. All achieved VL < 50 copies/ml at week 96/prior discontinuation, with no VF. D/C/F/TAF has a high barrier to resistance; no darunavir, primary PI, or tenofovir RAMs occurred through 96 weeks in AMBER and EMERALD. In EMERALD, baseline archived darunavir, emtricitabine, and tenofovir RAMs in patients with prior VF did not preclude virologic response. Highlights: In the Phase 3 AMBER (treatment‐naïve patients) and EMERALD (virologically suppressed treatment‐experienced patients) studies through week 96, almost no resistance mutations related to the study drugs were observed: no darunavir, primary protease inhibitor or tenofovir resistance‐associated‐mutations (RAMs) occurred post‐baseline in 1125 patients continuing on the once‐daily, single‐tablet regimen (STR), darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg or in 715 patients switching to D/C/F/TAF. The emtricitabine RAM, M184I/V, was detected in only one patient in each arm of AMBER. In EMERALD in the patients with prior virologic failure and baseline genoarchive data who received D/C/F/TAF, baseline archived darunavir, emtricitabine, and tenofovir RAMs, including those with predicted antiretroviral resistance, did not preclude virologic response. The D/C/F/TAF once‐daily STR provides a convenient treatment option, combining the efficacy and high barrier to resistance of darunavir with the safety advantages of TAF for treatment‐naïve and ‐experienced adults living with HIV‐1.